2010 8th International Pipeline Conference, Volume 2 2010
DOI: 10.1115/ipc2010-31237
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Wall Seamless Line Pipe X70–X80 for Sour Service Applications

Abstract: The continued shift of exploration and production to deep water fields will require the industry to develop alternative pipe solutions to cope with the challenging demands of these exploration regions. Because of the complexity of exploration conditions in deep water fields, e.g. high pressures, low temperature and sour reservoirs, higher grades and heavier wall thickness in combination with low temperature toughness and suitability for sour service are required. The Vallourec&Mannesmann Tubes’s alloying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Stringer-shaped inclusions are known to cause anisotropy in mechanical properties such as tensile ductility and fracture toughness [26]. Variations in grain size and grain shape along different directions can also cause anisotropy [32]. Another study [46] suggested, based on an analysis of texture intensities, that the anisotropy of toughness at room temperature might be attributed to the variation in the volume fraction of the {110} plane, with an angle to the circumferential direction.…”
Section: Charpy Impact Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stringer-shaped inclusions are known to cause anisotropy in mechanical properties such as tensile ductility and fracture toughness [26]. Variations in grain size and grain shape along different directions can also cause anisotropy [32]. Another study [46] suggested, based on an analysis of texture intensities, that the anisotropy of toughness at room temperature might be attributed to the variation in the volume fraction of the {110} plane, with an angle to the circumferential direction.…”
Section: Charpy Impact Valuesmentioning
confidence: 99%
“…During plastic deformation due to cold or hot work, grains are elongated in the direction of the applied stress. Therefore, the ferrite grain size varies in different directions, resulting in anisotropy in mechanical properties [28,32]. It is observed that grains of perlite and ferrite are usually oriented in the directions of lamination.…”
Section: Microstructures Obtained and Hr Valuesmentioning
confidence: 99%
See 1 more Smart Citation